Sindrom Horner : Rusaknya Jaras Okulosimpatetik - Fitriyani, Fitriyani; Melissa Dwi Mayang Sari; Betsheba, Betsheba (CV. Jasa Sukses Abadi, 2024)
Horner's syndrome is a group of symptoms consisting of a slightly drooping upper eyelid (ptosis) and a smaller pupil (miosis) on the affected side (ipsilateral), less commonly accompanied by a lack of sweat production (anhidrosis) over the ipsilateral eyebrow or face. Horner’s syndrome can be congenital, acquired, or inherited disorder, but the cause is sometimes unknown. Based on the anatomical location of the underlying pathological process, Horner's syndrome is classified into central, preganglionic, and postganglionic. Although in most cases clinical examination may predict the etiology, in other cases pharmacological testing can help in localizing the lesion. Pharmacological testing agents used in the diagnosis of Horner's syndrome include apraclonidine, cocaine, hydroxyamphetamine, or phenylephrine. Imaging approaches such as targeted Magnetic Resonance Imaging (MRI) or Computed Tomography Angiography (CTA) are recommended, given the financial burden of imaging the entire oculosympathetic pathway. This article reviews the clinical signs and symptoms as well as the pharmacological and imaging modalities that can help in the diagnosis and localization of Horner's syndrome and the cause of the condition.